The Decline of Deep Brain Stimulation for Obsessive–Compulsive Disorder Following FDA Humanitarian Device Exemption Approval - Pinckard-Dover, Heather; Ward, Herbert; Foote, Kelly D. (Frontiers in Surgery, 2021)
In February 2009, the FDA granted Humanitarian Device Exemption (HDE) for deep brain stimulation (DBS) in the anterior limb of the internal capsule (ALIC) for the treatment of treatment refractory obsessive-compulsive disorder (OCD). Despite its promise as a life altering treatment for patients with debilitating OCD, the use of DBS for the treatment of OCD is now rarely performed even at busy referral centers. We sought to identify factors hindering OCD patients from receiving DBS therapy. University of Florida (UF) clinical research databases were queried to identify patients evaluated as potential candidates for OCD DBS from January 1, 2002 to July 30, 2020. A retrospective review was performed to obtain demographic information, data related to their OCD, payor source, study participation, evaluation prior to or after HDE approval, and any stated factors prohibiting surgical intervention. Out of 25 patients with severe OCD identified as candidates for DBS surgery, 15 underwent surgery. After the HDE, only 9 out of 18 identified candidates were treated. Seven of the 9 were funded by Medicare, 1 paid out of pocket, and 1 bait and switch. Of the 10 patients not treated, 7 patients—all with private health insurance—were approved for surgery by the interdisciplinary team but were unable to proceed with surgery due to lack of insurance coverage, 1 decided against surgical intervention, 1 was excluded due to medical comorbidities and excessive perceived surgical risk, and no clear reason was identified for 1 patient. Based on compelling evidence that DBS provides substantial improvement in 2 out of 3 patients with treatment refractory OCD, the FDA approved this procedure under a HDE in 2009. A careful review of our experience with OCD DBS shows that since the HDE approval, only 50% of the severe OCD patients (9 of 18) have been able to access the therapy. We found the most common limiting factor to be failure of private insurance policies to cover DBS for OCD. We have identified an inherent discrimination in the US healthcare system and urge policy makers, insurance companies, and hospital administrations to recognize this health care disparity and seek to rectify it.